A Vector Based on the Chicken Hypersensitive Site 4 Insulator Element Replicates Episomally in Mammalian Cells - Zhang, Xi; Wang, Xiao-Yin; Jia, Yan-Long; Guo, Xiao; Wang, Yan-Fang; Wang, Tian-Yun (Current Gene Therapy, 2016)
Background: Gene therapy in mammalian cells requires vectors exhibiting long-term stability and high expression. Episomal gene expression vectors offer a safe and attractive alternative to those that integrate into the host cell genome. Materials & Methods: In the present study, we developed a new episomal vector based on the insulator, chicken hypersensitive site 4 (cHS4). The cHS4 element was artificially synthesized, cloned into the pEGFP-C1 vector, and used to transfect Chinese hamster ovary (CHO) and human Chang liver cells. The stably transfected cell colonies were further cultured in either the presence or absence of G418 selection. Fluorescence in situ hybridization (FISH) analysis and vector rescue experiments demonstrated that the vector replicated episomally in both CHO and human Chang liver cells. Compared with episomal vectors mediated by matrix attachment region sequences, the cHS4 element-containing vector yielded increased transgene expression levels, transfection efficiency, and stability during long-term culture. The vector was present at a very low copy number in the cells and was stably maintained over more than 100 generations without selection pressure. Conclusion: In conclusion, apart from a few free vector forms, the cHS4-containing vector mainly replicates episomally in mammalian cells and out- performs comparable systems in terms of yielding both higher expression levels and stability levels.
Keywords: Insulator element